Soil acidification and the importance of liming agricultural soils with particular reference to the United Kingdom - Goulding, K. W. T. (Soil use and management, 2016)
Soil acidification is caused by a number of factors including acidic precipitation and the deposition from the atmosphere of acidifying gases or particles, such as sulphur dioxide, ammonia and nitric acid. The most important causes of soil acidification on agricultural land, however, are the application of ammonium‐based fertilizers and urea, elemental S fertilizer and the growth of legumes. Acidification causes the loss of base cations, an increase in aluminium saturation and a decline in crop yields; severe acidification can cause nonreversible clay mineral dissolution and a reduction in cation exchange capacity, accompanied by structural deterioration. Soil acidity is ameliorated by applying lime or other acid‐neutralizing materials. ‘Liming’ also reduces N2O emissions, but this is more than offset by CO2 emissions from the lime as it neutralizes acidity. Because crop plants vary in their tolerance to acidity and plant nutrients have different optimal pH ranges, target soil pH values in the UK are set at 6.5 (5.8 in peaty soils) for cropped land and 6.0 (5.3 in peaty soils) for grassland. Agricultural lime products can be sold as ‘EC Fertiliser Liming Materials’ but, although vital for soil quality and agricultural production, liming tends to be strongly influenced by the economics of farming. Consequently, much less lime is being applied in the UK than required, and many arable and grassland soils are below optimum pH.